2014
DOI: 10.1111/joor.12212
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ADL on recovery of swallowing function in stroke patients after acute phase

Abstract: This study aimed to examine the association between the degree of recovery from dysphagia and changes in functional independence measure (FIM) items in stroke patients after acute phase by conducting a historical cohort study, because none explains the effects of activities of daily living (ADL) on recovery of swallowing function. Study patients included hospitalised stroke patients after acute phase in whom dysphagia was confirmed (n = 72). Change in nutritional intake method score was examined for associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 40 publications
3
18
1
Order By: Relevance
“…Older adult patients with poor ADL are thought to have declined eating ability, according to the results of this current study. Previous studies reported that dysphagic patients often show poor ADL, similar to the present results . Additionally, it is known that sarcopenia can be caused by inactivity .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Older adult patients with poor ADL are thought to have declined eating ability, according to the results of this current study. Previous studies reported that dysphagic patients often show poor ADL, similar to the present results . Additionally, it is known that sarcopenia can be caused by inactivity .…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies reported that dysphagic patients often show poor ADL, similar to the present results. 26,27 Additionally, it is known that sarcopenia can be caused by inactivity. 24,28 Considering the possibility that patients who consume TMD might be diagnosed with sarcopenic dysphagia, it is convincing that both low FIM score and decreased SMI are related to TMD.…”
Section: Discussionmentioning
confidence: 99%
“…While essential for enjoying meals, oral food intake may also play an important role in preventing respiratory infections such as pneumonia. Several studies have reported that orally fed patients have higher activity of daily living (Nakayama et al, 2014) and quality of life (Hong and Yoo, 2017) than tube-fed patients, highlighting the physiological and psychosocial benefits of oral food intake. In previous studies comparing the oral flora of patients fed via the two routes, the proportion of pathological bacteria such as Streptococcus agalactiae was increased in patients fed through a tube (Leibovitz et al, 2003;Takeshita et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Through effective rehabilitation, almost all elderly patients are able to fully recover activities of daily living (ADL), and are then discharged back to their homes. A cross-sectional study showed that there is a significant relationship between improvement of swallowing function and recovery of ADL in stroke patients [18]. On the other hand, sometimes elderly patients cannot fully improve functional performance even after receiving the same rehabilitation, although the exact reason is still not elucidated.…”
Section: Effects Of Oral Function On the Improvement Of Functional Camentioning
confidence: 99%